Structural characterization of the Saccharomyces cerevisiae autophagy regulatory complex Atg17-Atg31-Atg29 - Chew, Leon H (Autophagy, 2013)
Atg17, in complex with Atg29 and Atg31, constitutes a key module of the Atg1 kinase signaling complex and functions as an important organizer of the phagophore assembly site in the yeast Saccharomyces cerevisiae. We have determined the three-dimensional reconstruction of the full S. cerevisiae Atg17-Atg31-Atg29 complex by single-particle electron microscopy. Our structure shows that Atg17-Atg31-Atg29 is dimeric and adopts a relatively rigid and extended “S-shape” architecture with an end-to-end distance of approximately 345 Å. Subunit mapping analysis indicated that Atg17 mediates dimerization and generates a central rod-like scaffold, while Atg31 and Atg29 form two globular domains that are tethered to the concave sides of the scaffold at the terminal regions. Finally, our observation that Atg17 adopts multiple conformations in the absence of Atg31 and Atg29 suggests that the two smaller components play key roles in defining and maintaining the distinct curvature of the ternary complex.